Harnessing Nitrous Oxide for Sustainable Methane Activation: A Computational Exploration of CNC-Ligated Iron Catalysts - Bruce M. Prince (Methane)
This study employs DFT at the APFD/def2-TZVP level, with SMD solvation in THF, to investigate the catalytic activation of methane by [(κ3-CNC)Fe(N₂O)]2+ cation complexes. The catalytic mechanism encompasses three key steps: oxygen atom transfer (OAT), hydrogen atom abstraction (HAA), and oxygen radical rebound (ORR). The computational results identify OAT as the rate-determining step, with activation barriers of −10.2 kcal/mol and 5.0 kcal/mol for κ1-O- and κ1-N-bound intermediates in the gas and solvent phases, respectively. Methane activation proceeds via HAA, with energy barriers of 16.0–25.2 kcal/mol depending on the spin state and solvation, followed by ORR, which occurs efficiently with barriers as low as 6.4 kcal/mol. The triplet (S = 1) and quintet (S = 2) spin states exhibit critical roles in the catalytic pathway, with intersystem crossing facilitating optimal reactivity. Spin density analysis highlights the oxyl radical character of the FeIV=O intermediate as being essential for activating methane’s strong C–H bond. These findings underscore the catalytic potential of CNC-ligated iron complexes for methane functionalization and demonstrate their dual environmental benefits by utilizing methane and reducing nitrous oxide, a potent greenhouse gas.